Nurse educators' suggestions for a digital educational resource suitable for undergraduate student nurses' placement studies: Qualitative empirical research - Monika Ravik; Ingunn Aase; Kristin Akerjordet; Kristin Laugaland; Marianne Thorsen Gonzalez (Wiley, 2023)
Abstract Aims To explore and describe nurse educators' suggestions regarding a digital educational resource addressing quality in placement studies for first‐year student nurses in nursing homes. Design A qualitative, explorative, and descriptive research design. Methods Focus group interviews with eight nurse educators and individual interviews with six nurse educators. The interviews were audio‐recorded and transcribed verbatim; subsequently, data were analysed in lines with content analysis as described by Graneheim and Lundman. Results The analysis revealed three main categories: 'Suggestions for a digital educational resource to strengthen and support nurse educators' role in follow‐up students', 'Suggestions for a digital educational resource to complement and support interaction between stakeholders in placement', and 'Suggestions for a digital educational resource to facilitate student nurses' learning processes'. The categories were captured by the overarching theme, 'A digital educational resource facilitating interaction between stakeholders and students' learning processes. Conclusion This study revealed nurse educators' suggestions regarding design elements, content, and use of a digital educational resource addressing placement studies for first‐year student nurses' in nursing homes. Implications for the profession and/or patient care: Nurse educators should be involved in designing, developing, and implementing digital educational resources aiming to support student learning in nursing education placement studies. Impact This study explored nurse educators' suggestions for a digital educational resource. They suggested a digital educational resource to strengthen and support their role, support interaction between stakeholders, and facilitate student nurses' learning processes. Further, they suggested a digital educational resource to be used as a supplement rather than as a replacement for nurse educators' physical presence in placements. Reporting method The Consolidated Criteria for Reporting Qualitative Research reporting guidelines were used. No Patient or Public Contribution.